Recent developments and applications of polymer monolithic stationary phases - Eeltink, Sebastiaan; Meston, Daniel; Svec, Frantisek (Analytical science advances, 2021)
This review highlights the current trends and the most recent advances in the field of preparation and application of organic polymer-based monolithic materials and covers literature published in 2020. A short historical background is provided and protocols to anchor monoliths covalently to the wall of the column/separation device are discussed. Furthermore, advances in tuning the macroporous structure and establishing its link to separation performance are conferred. Finally, method development and key applications using novel monolithic columns are discussed.
Keywords: bioanalysis; review; column technology; stationary phase